A technique for mechanical adjustment of DC motor by virtual model - Smerpitak, Krit; Naruvorn, Natarak; Pongswatd, Sawai; Ukakimapurn, Prapart (My University, 2007)
This paper presents a technique to adjust and improve mechanical responses of DC Motor. The proposed technique uses math model for simulation to observe the transience and steady state response in no-load condition. Information derived from the simulation results can be applied to compensate the mechanical loss, inertia, viscous friction by feeding electrical energy. The test results of the compensation technique in this research can adjust and improve the response of speed and torque under reasonable tests. Moreover, this technique can apply to virtual load for Dynamometer. © ICROS.
Keywords: DC motor; Dynamometer; Math model; Mechanical; Simulation; Virtual